What can we learn from using formal patient‐reported outcome instruments to assess pain, functional impairment, anxiety, and depression in US adults with hemophilia?. (2nd March 2018) - Buckner, Tyler W.; Batt, Katharine; Cooper, David L.; Kempton, Christine L.
Abstract: People with hemophilia frequently suffer from arthropathy that leads to pain and functional impairment, ultimately resulting in reduced quality of life. The impact of pain and functional impairment on the lives of people with hemophilia was explored in the Pain, Functional Impairment, and Quality of Life (P‐FiQ) study. Various patient‐reported outcome (PRO) instruments were employed to assess the effect of pain and functional impairment on multiple aspects of health in people with hemophilia. The results presented in this supplement include detailed observations from PRO instruments regarding pain, functional impairment, anxiety, and depression, an analysis of the differences in health‐related quality of life across subgroups of patients defined by demographic and treatment‐related characteristics, and results of a modeling analysis to identify patient factors which influence perceptions of pain and functional impairment, independent of joint status. These data provide insights into how the results from PRO assessments may be used to evaluate outcomes for people with hemophilia in the clinical and research settings.